2003
DOI: 10.1111/j.1467-8292.2003.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Junior High Schools and the Role of Proprietary Structure

Abstract: In this paper we deal with the role of proprietary structure in explaining efficiency within the Italian school industry. We analyze a sample of 497 schools located in Piemonte, a region in the North-Western part of the country, distinguishing between public, private for-profit and private nonprofit schools. In stage one of the analysis, we provide robust estimates of efficiency scores, using the two most widely known techniques in applied works, namely Data Envelopment Analysis (DEA) and Stochastic Frontiers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 15 publications
(15 reference statements)
1
27
0
1
Order By: Relevance
“…The principal results obtained in this regard indicate the special importance of household socio-economic and cultural characteristics in explaining student This conclusion is in line with those reached in other, international, studies, where private high schools are shown to be inefficient compared to their public counterparts (Braun, Jenkins & Grigg (2006); Lubienski & Lubienski (2006); Barbetta & Turati, 2003;Kirjavainen & Loikkanen, 1998) 11 .…”
Section: Discussionsupporting
confidence: 76%
“…The principal results obtained in this regard indicate the special importance of household socio-economic and cultural characteristics in explaining student This conclusion is in line with those reached in other, international, studies, where private high schools are shown to be inefficient compared to their public counterparts (Braun, Jenkins & Grigg (2006); Lubienski & Lubienski (2006); Barbetta & Turati, 2003;Kirjavainen & Loikkanen, 1998) 11 .…”
Section: Discussionsupporting
confidence: 76%
“…Barbetta and Turati, 2003;Grosskopf et al, 2009). However, most of the efficiency studies look at different units of observation, and conclude that efficiency scores vary greatly among the units of observation (Barbetta and Turati, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Most contributions focus on a specific school cycle (the primary or secondary) and usually refer to a limited sample of schools. These are often schools of a same region or specific area (Barbetta and Turati 2003;Tyagi et al 2008;Maragos and Despotis 2004;Ruggiero 1996;Ruggiero and Vitaliano 1999) or small national samples (usually <500 schools).…”
Section: Introductionmentioning
confidence: 99%
“…As for inputs, a first strand of work is based mainly on human resources, i.e. the number of teachers and technical and administrative staff employed by schools (Essid et al 2009;Oliveira and Santos 2005;Maragos and Despotis 2004;Barbetta and Turati 2003). Other work focuses on the provision of financial resources and equipment (Agasisti 2009;Aaltonen et al 2006), while a third line also includes variables relating to socio-economic and cultural background of students or the school (Agasisti et al 2012;Tyagi et al 2008;Portela and Camanho 2007;Mancebon-Torrubia et al 2010;Ruggiero and Vitaliano 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation